President's Page. (2nd December 2016) - Caidi, Nadia
Abstract : EDITOR'S SUMMARY In her final message as ASIS&T president, Nadia Caidi extends thanks to the conference co‐chairs and many others who have contributed to a successful 2016 Annual Meeting in Copenhagen, the first beyond North America. Caidi notes the strong financial health of the Association and the hiring of the Association's first communications officer. Numerous efforts have been made toward priority goals for the year: outreach and engagement with members and the wider information science community and internal knowledge management. An Executive Director Task Force has been formed to find a successor to Dick Hill, considering organizational and financial status, strategic planning and oversight by either an executive director or an association management firm. Members are invited to share ideas and voice their opinions on issues of common interest as the Association moves forward.